Eficiencia productiva y económica de cinco tipos de sistemas de producción para maíz (Zea mays L.) variedad INIAP 111 con enfoque de agricultura de conservación, en LaguacotoIII, provincia Bolívar - Chillo Chillo, Marco Vinicio (2023)
Conservation agriculture is a farming system that encourages minimal mechanical soil disturbance (ie no-till cultivation), maintenance of permanent soil cover, and crop diversification. Regarding conservation agriculture (CA), in 2016 more than 155 million hectares in the world have adopted conservation methods as part of their productive strategy. In the Bolívar province, the cultivation of soft corn is the most important component of the local production systems, with an estimated area of 38,000 hectares distributed in the cantons of Guaranda, Chimbo, San Miguel and Chillanes. In the Bolívar Province, one of the main causes for the deterioration of ecosystems is conventional agriculture, due to the increase in areas with monocultures, the indiscriminate use and over doses of toxic agrochemicals, the elimination of plant cover, burning of crop residues, the excessive use of agricultural machinery in hillside conditions directly affects the deterioration of natural resources. Therefore, the objective of this research was to evaluate the productive and economic efficiency of five types of production systems in corn variety INIAP 111 with a conservation agriculture approach to assess the effect of the increase in the yield of soft corn in the different production systems. production, determine the economic efficiency of the different soft corn production systems and establish a technological alternative based on the productive and economic response of corn for the agroecological zone under study. The variables were evaluated: Percentage of Emergence, Number of plants per plot); Days to harvest in corn; stem diameter; Plant height; Ear insertion height; Number of plants with ear; Number of plants without ear; Percentage of plants with two ears; Ear topping; Days to dry harvest; Ear diameter; Ear length; Field weight per plot; Shelling; Grain moisture percentage and Yield in kg/ha (RH). The treatments under study were five production systems based on: Rotation, Tillage and Stubble Management. The type of analysis that was carried out was; Tukey's test at 5% to compare treatment averages. Analysis of Correlation and Linear Regression and Analysis of the benefit-cost relationship B/C. The results obtained in each of the treatments did not show statistical differences, but they did show numerical differences in each of the averages of the agronomic components evaluated. The most efficient tillage system in terms of the agronomic yield component was conventional tillage without residues, with 3678.2 kg/ha with a benefit/cost ratio of 0,65, which means that for every dollar invested, corn producers have a profit of 0,65 with this production system. The agronomic components that increased the yield of the INIAP-111 maize crop was: Percentage of emergence, Ear insertion height, Ear length, Number of plants with ear while Number of plants without ear reduced corn yield.